Finite-rank intermediate Hankel operators on the Bergman space - Takahiko Nakazi; Tomoko Osawa (International Journal of Mathematics and Mathematical Sciences)
Let L2=L2(D,r dr dθ/π) be the Lebesgue space on the open unit disc and let La2=L2∩ℋol(D) be the Bergman space. Let P be the orthogonal projection of L2 onto La2 and let Q be the orthogonal projection onto L¯a,02={g∈L2;g¯∈La2,   g(0)=0}. Then I−P≥Q. The big Hankel operator and the small Hankel operator on La2 are defined as: for ϕ in L∞, Hϕbig(f)=(I−P)(ϕf) and Hϕsmall(f)=Q(ϕf)(f∈La2). In this paper, the finite-rank intermediate Hankel operators between Hϕbig and Hϕsmall are studied. We are working on the more general space, that is, the weighted Bergman space.